THE PHENOMENON OF FLEXING BEHAVIOUR ON SOCIAL MEDIA EFFECTS ON COLLEGE STUDENTS’ PERSONALITY - Raihana Sakdiyah; Alemina Br. Perangin-angin (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
Flexing is a term or slang that defines the conduct of excessive self-promotion when someone is displaying something. This might include the practice of often releasing information after acquiring a new item, the technique of constantly sharing successes on social media or the behaviour of frequently uploading vacation photographs. The qualitative research in this study, which adopts a grounded theory technique, focuses on the flexing behaviour demonstrated by college students as participants. This study aims to "understand how different types of flexing behaviour effect college students' personalities." display disturbingly high rates of flexing behaviour because of their lifestyle and peer-reported behaviours. This flexing behaviour may be prohibited if it interferes with other activities, causes injury to others, or affects people's ideas of themselves.